Long-term stability of ready-to-use epinephrine 0.02 mg/mL injection solution in 50 mL glass vials - Heeb Rita Marina; Erdnüß Frank; Reichhold Julia; Krämer Irene (De Gruyter, 2022)
In adult intensive care patients, epinephrine is mostly administered by continuous injection with syringe pumps. The objective of this study was to investigate the physicochemical stability of pharmacy prepared ready-to-use epinephrine (E) 0.02 mg/mL injection solutions (total volume 50 mL) for assigning shelf-life.